2002
DOI: 10.1074/jbc.m206638200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with GM130 during HERG Ion Channel Trafficking

Abstract: Many mutations in the Human Ether-à -go-go-Related Gene (HERG) cause type 2 congenital long QT syndrome (LQT2) by disrupting trafficking of the HERG-encoded potassium channel. Beyond observations that some mutations trap channels in the endoplasmic reticulum, little is known about how trafficking fails. Even less is known about what checkpoints are encountered in normal trafficking. To identify protein partners encountered as HERG channels are transported among subcellular compartments, we screened a human hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…It is possible that residues 860 -899 eliminate the interaction between HERG and GM130. However, dissociation of HERG ⌬860 -899 and GM130 cannot explain the phenotypes reported here because this interaction is not required for the perfunctory delivery of HERG channels to the plasma membrane (32).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is possible that residues 860 -899 eliminate the interaction between HERG and GM130. However, dissociation of HERG ⌬860 -899 and GM130 cannot explain the phenotypes reported here because this interaction is not required for the perfunctory delivery of HERG channels to the plasma membrane (32).…”
Section: Discussionmentioning
confidence: 56%
“…In addition, previous studies have indicated that multiple regions throughout the subunits are required for assembly of ion channels and it is unlikely that deletion or a point mutation of selected residues of HERG would completely abolish its interaction with an auxiliary subunit (30,31). Interestingly, residues 860 -899 fall between two non-contiguous regions of HERG involved in the interaction between HERG and GM130, proposed to facilitate HERG transport (32). It is possible that residues 860 -899 eliminate the interaction between HERG and GM130.…”
Section: Discussionmentioning
confidence: 99%
“…6B). This result may suggest fundamental differences between the cellular processing of Q2 subunits and the K ϩ channels subunits encoded by the human Ether-a-gogo-Related gene 1 (hERG1), which have been shown to interact with GM-130 in biochemical, morphological, and functional studies (32). Closer inspection to the data revealed a weak but convincing cell-surface labeling only in EGFP-Q2-transfected cells (as indicated by the arrows).…”
Section: Electrophysiological and Biochemical Analysis Of Kcnq2 C-termentioning
confidence: 96%
“…A yeast two-hybrid screen revealed the cis-Golgi protein GM130 was a hERG binding partner using the carboxyl terminus as bait 77 . The interaction was disrupted by deletions of the C-terminal-most 117 amino acids.…”
Section: Other Cytoplasmic Regionsmentioning
confidence: 99%
“…Interestingly, the disrupting LQT2 mutations reside in the CNBh domain. The mutant hERG proteins are trafficking-defective, as if hERG channel exit from the ER or access to the Golgi requires the integrity of two regions, one of poor secondary structure, and the other a highly ordered domain 77 .…”
Section: Other Cytoplasmic Regionsmentioning
confidence: 99%